Pathways and efficiency of nitrogen attenuation in wastewater effluent through soil aquifer treatment. (1st November 2022) - Abu, Alex; Carrey, Raúl; Valhondo, Cristina; Domènech, Cristina; Soler, Albert; Martínez-Landa, Lurdes; Diaz-Cruz, Silvia; Carrera, Jesús; Otero, Neus
Abstract: Soil Aquifer Treatment (SAT) is used to increase groundwater resources and enhance the water quality of wastewater treatment plant (WWTP) effluents. The resulting water quality needs to be assessed. In this study, we investigate attenuation pathways of nitrogen (N) compounds (predominantly NH4 + ) from a secondary treatment effluent in pilot SAT systems: both a conventional one (SAT-Control system) and one operating with a permeable reactive barrier (PRB) to provide extra dissolved organic carbon to the recharged water. The goal is to evaluate the effectiveness of the two systems regarding N compounds by means of chemical and isotopic tools. Water chemistry (NO3 −, NH4 +, Non-Purgeable Dissolved Organic Carbon (NPDOC), and O2 ) and isotopic composition of NO3 − ( ẟ 15 N–NO3 - and ẟ 18 O–NO3 - ) and NH4 + ( ẟ 15 N–NH4 + ) were monitored in the inflow and at three different sections and depths along the aquifer flow path. Chemical and isotopic results suggest that coupled nitrification-denitrification were the principal mechanisms responsible for the migration and distribution of inorganic N in the systems and that nitrification rate decreased with depth. At the end of the study period, 66% of the total N in the solution was removed in the SAT-PRB system and 69% in the SAT-Control system, measured at the outlet of the systems. The residual N in solution in the SAT-PRB system had an approximately equal proportion of N–NH4 + and N–NO3 - while in the SAT-Control system, the residual N in solution was primarily N–NO3 - . Isotopic data also confirmed complete NO3 − degradation in the systems from July to September with the possibility of mixing newly generated NO3 − with the residual NO3 − in the substrate pool. Highlights: We applied isotopic tools in pilot soil aquifer treatment systems to evaluate the N cycle. Simultaneous nitrification-denitrification was the principal N attenuation pathway. Nitrification occurred at the top of the system due to vertical diffusion of O2 . Denitrification was enhanced by the increase of dissolved organic carbon and temperatures. Limitations in using isotopic tools to quantify multiple reactions were observed.